Aplikasi Mikrosimbions Spons Laut Sebagai Biomaterial Pereduksi Toksisitas Logam Berat Kromium (Cr) - Marzuki, Ismail; Ashari, M. Iksan; Marzuki, Andi Asdar; Angela, Andi (Al-Kimia, 2019)
The vulnerable marine environment is polluted by various types of heavy metals due to human and natural activities. One of the marine biota sponges can carry out heavy metal adsorption functions, so the life of the sponge must be well maintained. The application of sponge micro symbiont adsorption method aims to reduce the toxicity of chromium metal. Absorption stage: culture isolates code Sp1, Sp2, Sp3, Petrosia sponge (Strongylophore) Corticata symbionts, phenotypic and genotypic characterization, suspension symbionts were formed, interacted with 100 ppm of 1: 1 ratio chromium solution Interaction time variation 5, 10, 15, 20, 25 days, extracted. The remaining non-reduced chromium was analyzed using AAS. Observation of reduction, gas, pH, optical density parameters. The results of phenotypic characterization showed that 3 sponge symbiont isolates reacted with lactose, catalase, MR, VP and citrate. Genotypes of Pseudomonas stutzeri isolates, strain Sp1 are RCH2, Sp2 code SLG510A3-8, and Sp3 code GLB197. The reduction parameters reached a contact period of 5-15 days, the performance of the symbionts in the reduction of chromium metal toxicity in the range of 62.34 ppm to 70.47 ppm was equivalent to the reduction rate of 60.16 to 69.09% concentration.